Students’ socio-psychological factors as predictors of achievement in senior secondary school english language (1999)
The study sought to explain senior secondary (SS) students' achievement in English language using some student socio-psychological variables: home language; locus of control; study habits; career aspiration; interest in schooling; self-concept; and test anxiety. Data on the relevant variables was collected from 448 SSII students in Akinyele and Ibadan North Local Government Areas of Oyo State, Nigeria. Data analysis involved using stepwise multiple regression to examine the relationship between English language achievement and the seven independent variables. The results show that the socio-psychological variables, when taken together, effectively predicted English language achievement among senior secondary school students: The results also indicate that each of the variables contributed significantly to the prediction; and that self- concept is the most potent contributor. These findings have implications for English language teachers and counselors who are interested in solving problems of secondary school students' underachievement in English language.